Rapid compact jet quenching in the Galactic black hole candidate X-ray binary MAXI J1535−571. Issue 4 (1st September 2020) - Russell, T D; Lucchini, M; Tetarenko, A J; Miller-Jones, J C A; Sivakoff, G R; Krauß, F; Mulaudzi, W; Baglio, M C; Russell, D M; Altamirano, D; Ceccobello, C; Corbel, S; et al.
ABSTRACT: We present results from six epochs of quasi-simultaneous radio, (sub-)millimetre, infrared, optical, and X-ray observations of the black hole X-ray binary MAXI J1535−571. These observations show that as the source transitioned through the hard–intermediate X-ray state towards the soft–intermediate X-ray state, the jet underwent dramatic and rapid changes. We observed the frequency of the jet spectral break, which corresponds to the most compact region in the jet where particle acceleration begins (higher frequencies indicate closer to the black hole), evolves from the infrared band into the radio band (decreasing by ≈3 orders of magnitude) in less than a day. During one observational epoch, we found evidence of the jet spectral break evolving in frequency through the radio band. Estimating the magnetic field and size of the particle acceleration region shows that the rapid fading of the high-energy jet emission was not consistent with radiative cooling; instead, the particle acceleration region seems to be moving away from the black hole on approximately dynamical time-scales. This result suggests that the compact jet quenching is not caused by local changes to the particle acceleration, rather we are observing the acceleration region of the jet travelling away from the black hole with the jet flow. Spectral analysis of the X-ray emission shows a gradual softening in the few days before the dramatic jet changes, followed by a more rapid softening ∼1–2 d after the onset of the jet quenching.